Psychopathological Features of Bipolar Depression: Italian Validation of the Bipolar Depression Rating Scale (I-BDRS) - Bruschi, Angelo; Mazza, Marianna; Camardese, Giovanni; Calò, Salvatore; Palumbo, Claudia; Mandelli, Laura; Callea, Antonino; Gori, Alessio; Di Nicola, Marco; Marano, Giuseppe; Berk, Michael; di Sciascio, Guido; et al. (Frontiers in Psychology, 2018)
Background: Aim of the study was the validation of the Bipolar Disorder Rating Scale (BDRS) in an Italian population. Secondary aim was the evaluation of differences between unipolar and bipolar depression and between bipolar I and II depressed patients. Method: 125 Bipolar Disorder and 60 Major Depressive Disorder patients were administered an Italian translation of the BDRS (I-BDRS), Hamilton Depression Rating Scale (HDRS), Montgomery-Asberg Depression Rating Scale (MADRS), Young Mania Rating Scale (YMRS) and Temperament and Character Inventory-Revised (TCI-R). Results: I-BDRS showed considerable validity and reliability. Factor analysis found 3 subscales, two linked to depressive symptoms and one to mixed symptoms. Measures concerning depression (MADRS and HAM-D) were positively related to the I-BDRS's subscales, but mostly to the two subscales measuring depression. In mixed symptoms, the mean of the bipolar group was significantly higher than the unipolar group suggesting that the BDRS was able to distinguish between unipolar and bipolar depressed patients. Conclusion: I-BDRS is a valid scale for the measurement of depression in BD patients, with a notable internal consistency (Cronbach's α 0.82), a significant consistency between items/total (Cronbach's α from 0.80 to 0.82) and positive correlation with other scales (MADRS r = 0.67, p < 0.001; HDRS r = 0.81, p < 0.001; YMRS r = 0.46 p < 0.0001). The mixed state sub-scale shows usefulness in differentiating bipolar from unipolar patients. I-BDRS could be a sensitive tool, both in pure depression and in mixed states, and could be used in the everyday screening and treatment of Bipolar Disorder.